Corporate Governance. Entrepreneurial culture in favor of the creation of value and conflict prevention - Rodríguez-Jaraba, Rafael (2023)
The present article, more than centering in the study and analysis of dispute resolution mechanisms, will review in an academic and practical manner, the prevention of them by adopting principles of Corporate Governance, such as good faith, justice and equity and its mandates must be bound by efficiency, efectiveness and economy of every process an organization follows exercising their productive actitivies.